2017
DOI: 10.1038/s41598-017-07389-0
|View full text |Cite
|
Sign up to set email alerts
|

Value of shear wave arrival time contour display in shear wave elastography for breast masses diagnosis

Abstract: To evaluate the diagnostic performance of shear wave arrival time contour (SWATC) display for the diagnosis of breast lesions and to identify factors associated with the quality of shear wave propagation (QSWP) in breast lesions. This study included 277 pathologically confirmed breast lesions. Conventional B-mode ultrasound characteristics and shear wave elastography parameters were computed. Using the SWATC display, the QSWP of each lesion was assigned to a two-point scale: score 1 (low quality) and score 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Different researches have been conducted to examine the quantitative elasticity values in the diagnostic performance of thyroid nodules [ 12 ], metastatic and nonmetastatic cervical lymph nodes [ 13 ], and acute pancreatitis [ 14 ]. In differentiating benign and malignant breast masses, there is an increasing trend to use VTQ measurement [ 15 , 16 ]. The mean SWV of the malignant neoplasms analyzed by Tozaki et al [ 17 ] was 1.81 m/s faster than that of benign masses (P<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Different researches have been conducted to examine the quantitative elasticity values in the diagnostic performance of thyroid nodules [ 12 ], metastatic and nonmetastatic cervical lymph nodes [ 13 ], and acute pancreatitis [ 14 ]. In differentiating benign and malignant breast masses, there is an increasing trend to use VTQ measurement [ 15 , 16 ]. The mean SWV of the malignant neoplasms analyzed by Tozaki et al [ 17 ] was 1.81 m/s faster than that of benign masses (P<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…1). The region in which the green color is absent on the shear wave quality map indicates where the shear wave is not detected because of patient motion and/or transducer motion during VTIQ image acquisition (Zhou et al 2017). Therefore, images in which the green color was absent within the Quality Map were excluded from the study.…”
Section: Bbm Shear Wave Velocity In Arfi Imagingmentioning
confidence: 99%
“…In a recent report, the standard deviation for the SWE mean was identified to be the strongest factor associated with the quality of shear wave propagation (Zhou et al 2017). Studies have also found that technical failures are not machine dependent, and for high SWE reliability, ultrasound devices should not be used interchangeably (Woo et al 2015).…”
Section: Discussionmentioning
confidence: 99%